TREN PERIKLANAN DI MEDIA SOSIAL - Tasruddin, Ramsiah (Komodifikasi, 2018)
In the ultimate moment, advertising scope as more as growth dynamically even more so important to be marketed through internet facility by online on a lot of social media. Advertising marketing by online willy nilly is urgent’s needs for information society, especially for business player such as investor or advertising producer. The dynamic growing of online advertising has made advertising marketing as more as competitive in the social media market too. One of that’s to apply the content marketing of the advertising products such as ultimate advertising marketing strategy.